The Problem of Information Security in Official Statistics - Osaulenko О. Н. (Statistics of Ukraine, 2017)
The official statistics have importance role in the problems of national information security; being an integral part of the social information space, it faces security-specific risks immanent in any kind of information system. It is emphasized that information security in the official statistical has to encompass all the phases and all the participants of the statistical production process, from the producers at the phase of data processing and storage to user security at the phase of data dissemination. Issues of statistical data confidentiality are analyzed as a fundamental principle of international and European statistics. It is demonstrated that the documents sharing functions among those concerned with the national statistical system, their responsibilities for statistical confidentiality and procedures for access to various types of information need to be elaborated and approved at legislative level. Apart from this, the system of administrative, technical and organizational measures providing for physical and logical protection of confidential data, in order to prevent their disclosure, in parallel with organizing the controlled access to data for research purposes has to be built and introduced in the statistical practice The respective approaches used in the statistical system need to be harmonized and set in conformity with the global practice. Subject to detailed analysis is the issue of statistical secrecy, discussed as a broad concept dealing with the necessity to protect individual data of the population, individual data of companies and classified information, which access may undermine political and social interests. It is emphasized that the Law of Ukraine “On State Statistics” fails to provide a comprehensive response to the problems of defining classified information and its protection procedures. The relationship of internationally recognized principles of statistical activities and information security attributes is substantiated, especially from the global information quality perspective. The conclusion is made that the statistical service, when interacting with users, needs to orient on the commonly accepted criteria for statistical data quality assessment, formulated in official international documents that have to be adapted by the national official statistics through elaborating and introducing respective legal acts.